Evaluating web-based cognitive-affective remediation in recent trauma survivors: study rationale and protocol. Issue 1 (1st January 2018) - Fine, Naomi B.; Achituv, Michal; Etkin, Amit; Merin, Ofer; Shalev, Arieh Y.
ABSTRACT: Background : The immediate aftermath of traumatic events is a period of enhanced neural plasticity, following which some survivors remain with post-traumatic stress disorder (PTSD) whereas others recover. Evidence points to impairments in emotional reactivity, emotion regulation, and broader executive functions as critically contributing to PTSD. Emerging evidence further suggests that the neural mechanisms underlying these functions remain plastic in adulthood and that targeted retraining of these systems may enhance their efficiency and could reduce the likelihood of developing PTSD. Administering targeted neurocognitive training shortly after trauma exposure is a daunting challenge. This work describes a study design addressing that challenge. The study evaluated the direct effects of cognitive remediation training on neurocognitive mechanisms that hypothetically underlay PTSD, and the indirect effect of this intervention on emerging PTSD symptoms. Method : We describe a study rationale, design, and methodological choices involving: (a) participants' enrolment; (b) implementation and management of a daily self-administered, web-based intervention; (c) reliable, timely screening and assessment of treatment of eligible survivors; and (d) defining control conditions and outcome measures. We outline the rationale of choices made regarding study sample, timing of intervention, measurements, monitoring participants' adherence, and ways to harmonize and retain interviewers' fidelity and mitigate eventual burnout by repeated contacts with recently traumatized survivors. Conclusion : Early web-based interventions targeting causative mechanisms of PTSD can be informed by the model presented in this paper.